Technical and Vocational Education and Technology Transfer: Departments of Electrical Engineering at the Public Authority for Applied Education and Training, PAAE&T, Kuwait, As A case Study - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
The role of technology transfer in technical and vocational education is significant since lecturers, trainers, and students can obtain the updated knowledge, skills, and attitudes that are currently being practice by local and international business and industries. Technology transfer can indeed close the gap between what is being learned and practice in technical and vocational institutions and the world of work. However, the success technology transfer in technical and vocational education perspective would depend entirely on the quality of management. It is their responsibility, when signing an agreement with internal or external providers of technology, to include calluses that enable academic staff in related specialty to interact positively and freely with the supplier on technology. In other terms, ensuring no clear or hidden restriction imposed by the supplier of technology to acquire the know-how and know-why that are embedded in the agreement. In this paper, I present some of the empirical results and observations which describe the interactions between the supplier of technology (Electrical Engineering System) and the recipient of the technology (PAAE&T) in the field of technology transfer. In other word, whether the PAAE&T have taken the opportunity, while building its new headquarter, in the transfer of technology from the supplier of electrical engineering system to its academic staff in its various Electrical Engineering Academic Departments at the PAAE&T colleges and institutions. The paper argues that, for effective and efficient transfer of technology, the recipient (PAAE&T) must ensure that the agreement with the supplier of Electrical Engineering System must include calluses that would allow the PAAE&T academic staff in its various Electrical Engineering Academic Departments in its various colleges and institutions to acquire the technology embedded in the agreement. The paper concludes that the transfer of technology and the building of a local scientific and technical infrastructure must be viewed by Kuwaiti decision-makers as a complementary to one another. Thus, reducing, to great extent, the level of dependence on expatriate, particularly in essential sector of the economy.